To Read or Not to Read Dickens in the Twenty-First Century: What If He Needed to Be Read Twice?, - Nathalie Jaëck (Cahiers Victoriens et Edouardiens)
In this paper I try to reassess Dickens by confronting his late novels to those of some eminent Adventure writers, Doyle, Stevenson, but also Conrad. Despite their seemingly widely different styles and literary aims, they all contribute to build, in the second half of the nineteenth century, a coherent and autonomous, though still quite furtive, literary movement, in between Realism and Modernism, a movement that I will attempt to define and circumscribe. I would like to show that Dickens’s novels resemble in many crucial respects those of these writers of Adventure, that they share the same crucial preoccupations with finding a way out of Realism, and experiment on different technical ways to dismiss the Realist system. I will of course concentrate on the ‘strange case’ of Charles Dickens, a case of ‘impure,’ or ‘self-dissolving’ Realism: in his fundamentally dual, self-contradicting novels, Dickens manages to build the most solid, coherent, incontestable texts, while he also develops, within the novels themselves, a dissident counterproposal, an intimate deconstruction. In this respect, Dickens, like his famous fellow literary adventurers, situates himself in a very intense literary period and contributes to creating it by writing ‘in the middle,’ in a still undefined theoretical space, away from Realism, but not yet caught in the Modernist system: they settle in the unstable state of imminence they historically find themselves in, and methodically explore its literary possibilities.